(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores gender-based differences in online purchasing behavior in Kanyakumari District, aiming to understand the factors influencing consumer preferences, satisfaction, and trust towards e-commerce platforms. With the rapid growth of online shopping, analyzing gender perspectives provides valuable insights for businesses to enhance their digital marketing strategies and customer experience. A structured survey was conducted among 300 respondents using a stratified random sampling technique. Data were analyzed using statistical tools like t-tests, chi-square tests, ANOVA and regression analysis to examine the significance of gender differences. The results indicate that males exhibit higher purchasing behavior, driven by product quality, brand reputation, and technological features. On the other hand, females prioritize factors like security, privacy, brand loyalty, and customer support. Demographic factors such as age, income, and education significantly influence purchasing behavior, with younger and middle-income groups showing higher engagement. Trust in payment security, satisfaction with product quality, and efficient customer support were identified as major factors contributing to female consumer satisfaction. The study concludes that e-commerce businesses can benefit from implementing gender-specific marketing strategies by focusing on trust-building measures, enhancing product quality, and providing personalized recommendations. These insights can aid in creating inclusive and customer-centric online shopping experiences, fostering brand loyalty and increased sales.